The overview of the radon and environmental characteristics measurements in the Czech show caves - Thinová, L; Froňka, A; Rovenská, K (Radiation protection dosimetry, 2015)
This paper focuses on the measurement and assessment of absorbed doses of radiation in caves of the Czech Republic, some of which exhibit high activity concentration of radon in air. Presented is an analysis and recommendations based on measurement results obtained in the underground caves over the past 12 y. The most important results for cave environments were as follows: integral radon monitoring using RAMARN detectors can provide more consistent results for calculating the effective dose; no major differences were shown in the average radon activity concentration during working time as opposed to non-working time; the unattached fraction of radioactive particles in air ranged from 0.03 to 0.6, with arithmetical average fp = 0.13; the direct dependence between equilibrium factor F and the size of the unattached fraction fp was described using the Log-Power expression ln(1/fp) = a*ln(1/F)(b); the calculated values for coefficients a and b were 1.85 and -1.096, respectively. The individual cave factor for each investigated underground area was calculated.
Keywords: Radiation Monitoring; Caves; geologické sedimenty; velikost částic; aerosoly; alfa částice; Humidity; Seasons; speleoterapie; teplota; Phase Transition; monitorování životního prostředí; jeskyně; Particle Size; Radiation Exposure; vlhkost; Alpha Particles; lidé; radioaktivní látky znečišťující půdu; Occupational Exposure; roční období; Speleotherapy; radon; Soil Pollutants, Radioactive; Radon; Temperature; Aerosols; monitorování radiace; radioaktivní látky znečišťující vzduch; pracovní expozice; Czech Republic; radiační expozice; Environmental Monitoring; změna skupenství; Česká republika; Geologic Sediments; radioaktivní látky znečišťující vodu; Water Pollutants, Radioactive; Air Pollutants, Radioactive; Humans